The Shakespeare book - Wells, Stanley, 1930- (London : Dorling Kindersley, 2015)
The Shakespeare Book is the perfect primer to the works of William Shakespeare, packed with witty illustrations and inspirational quotes. Covering every work, from the comedies of Twelfth Night and As You Like It to the tragedies of Julius Caesar and Hamlet, plus lost plays and less well-known works of poetry. Easy-to-understand graphics and illustrations bring the themes, plots, characters and language of Shakespeare to life. This includes illustrated timelines which offer an at-a-glance summary of the action for each play. With detailed plot summaries and an in-depth analysis of the major characters and themes, this is a brilliant, innovative exploration of the entire canon of Shakespeare plays, sonnets and poetry. Whether you're a Shakespeare scholar or a student of the great Bard, The Shakespeare Book offers a fuller appreciation of his phenomenal talent and lasting legacy.
Includes index.
Keywords: Shakespeare -- Characters